Small molecule tyrosine kinase inhibitors in pancreatic cancer - Sachin Gupta (Dove Medical Press, 2008)
Sachin Gupta, Bassel F El-RayesDepartment of Hematology/Oncology, Karmanos Cancer Institute, Wayne State University, MI, USAAbstract: Pancreatic cancer has proven to be chemo-resistant, with gemcitabine being the only cytotoxic agent approved for advanced pancreatic cancer since 1996. Tyrosine kinase inhibitors represent a newer generation of chemotherapeutic agents targeting specific tumor pathways associated with carcinogenesis including cell cycle control, signal transduction, apoptosis and angiogenesis. These agents present a more selective way of treating pancreatic cancer. Erlotinib is the prototype of the tyrosine kinase inhibitors with proven efficacy in advanced pancreatic cancer and has been recently approved in that setting. Multiple other tyrosine kinase inhibitors targeting the VEGFR, PDGFR, and Src kinases are in various phases of clinical trials testing. The preliminary results of these trials have been disappointing. Current challenges in pancreatic cancer clinical trials testing include improving patient selection, identifying effective combinations, improving the predictive value of current preclinical models and better study designs. This review summarizes the present clinical development of tyrosine kinase inhibitors in pancreatic cancer and strategies for future drug development.Keywords: pancreatic cancer, erlotinib, tyrosine kinase inhibitors